1971
DOI: 10.1037/h0031977
|View full text |Cite
|
Sign up to set email alerts
|

Fears as attitudes: Experimental reduction of fear through reinforcement.

Abstract: This study investigated the hypothesis that fears are attitudes and can he reduced through the use of positive reinforcement. Fear was defined behaviorally as an expression of avoidance responses in the presence of the phobic object (in this study a harmless snake). Two hundred undergraduate female 5s in introductory psychology courses were administered a 122-item Fear Survey Schedule. From this group, 76 5s were selected according to a preestablished criterion and randomly assigned to four treatment groups-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Further, the terminal anxiety decrements indicated that all groups were experiencing at least moderate emotional arousal while performing their most advanced approach responses at the posttreatment assessment. The failure of subjective anxiety scales to reflect significant changes at the end of treatment has also been reported by Lang and Lazovik (1963) and Suinn, Jorgensen, Stewart, and McGuirk (1971).…”
Section: Anxiety Decrements As a Function Oj Level Of Approach Responsesmentioning
confidence: 65%
“…Further, the terminal anxiety decrements indicated that all groups were experiencing at least moderate emotional arousal while performing their most advanced approach responses at the posttreatment assessment. The failure of subjective anxiety scales to reflect significant changes at the end of treatment has also been reported by Lang and Lazovik (1963) and Suinn, Jorgensen, Stewart, and McGuirk (1971).…”
Section: Anxiety Decrements As a Function Oj Level Of Approach Responsesmentioning
confidence: 65%
“…Marks and Gelder (1967) have shown that with aversion therapy, one can change attitudes toward deviant sexual objects from "highly positive" to neutral or even "moderately negative." Thus, while Suinn et al (1971) are to be congratulated for initiating research on this topic, one could conclude that their emphasis was misplaced. The changing of attitudes by the techniques of behavior modification is the more important aspect of this research area.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…This stance is not shared by the present author. Blanchard and Elkin (1973) have criticized the Suinn, Jorgensen, Stewart, and McGuirk (1971) research on statistical and theoretical grounds. This rejoinder systematically evaluates each of the criticisms.Blanchard and Elkin offered alternatives to the statistical analyses employed in the original research and drew alternative conclusions.…”
mentioning
confidence: 99%
“…This stance is not shared by the present author. Blanchard and Elkin (1973) have criticized the Suinn, Jorgensen, Stewart, and McGuirk (1971) research on statistical and theoretical grounds. This rejoinder systematically evaluates each of the criticisms.…”
mentioning
confidence: 99%